«Українськість» vs. «суржик»: українська культура у сприйнятті носіїв українсько-російського змішаного мовлення - Палінська, О.М. (Мовознавство, 2018)
У статті розглянуто взаємозв’язок між мовними кодами в контексті користування українсько-російським змішаним мовленням і ставленням до культури жителів Центральної України. На основі даних інтерв’ю та масштабного опитування з’ясовано, як респонденти розуміють поняття «культура», чи вважають вони українську культуру окремим феноменом та як ці сприйняття пов’язані з їхніми мовними преференціями — переважним використанням «чистих» ідіомів (української / російської) чи українсько-російського змішаного мовлення. This paper deals with the relationship between language codes and cultural attitudes
in the Central Ukraine with people regularly practicing Ukrainian-Russian mixed speech
(URMS). It is shown that URMS-speakers in comparison to other inhabitants of central
Ukraine are by no means ethnomarginals, not rooted in any of the cultures: Ukrainian or
Russian. Their opinions on the difference of the Ukrainian culture from others, especially
from the Russian one, as well as a set of cultural stereotypes coincide with the data of
respondents which use mainly «pure» Ukrainian language. In addition, people who use
mixed idioms do by and large not differ in their education or social status. URMS-speakers
are less inclined to see a threat to Ukrainian culture in the usage of Russian and the mixed
code, although they believe that the Ukrainian language is crucial for Ukrainian culture,
though to a somewhat lesser extent than other respondents. Like all the inhabitants of the
region, URMS-speakers have the opinion that «true» Ukrainians should speak Ukrainian,
nevertheless they judge it fairly possible to be Ukrainian and not to speak Ukrainian.
The choice of the preferred or primarily used linguistic code is not related to religious
beliefs of speakers. Respondents using or not using URMS equally often consider the
orthodox church to be a part of Ukrainian culture. The majority of all respondents do not
object to the mixed speech as an element of (especially comic) popular culture. In public
space, however, first of all in the linguistic behavior of politicians, URMS tends to be seen
negatively, though URMS-speakers are more inclined to accept URMS even here. When
it comes to the language on TV, on pages in the Internet and in books, newspapers and
magazines, no difference of preference with speakers and non-speakers of the URMS can
be stated for Ukrainian. URMS-speakers, however are more inclined than non-URMSspeakers
to consume media in Russian, which means that the former are more open
towards Russian media than the latter. The majority of the inhabitants of Central Ukraine
(URMS-speakers or not) are clearly in favor of the use of Ukrainian in public space and
strong supporters of Ukrainian culture, although quite often this is not supported by their
own linguistic practice or an active participation in cultural life.